Structural analysis of the Toll-like receptor 15 TIR domain - Kyung Yeol Ko; Wan Seok Song; Jeongho Park; Geun-Shik Lee; Sung-il Yoon (IUCrJ, 2023)
Toll-like receptors (TLRs) activate innate immunity in response to pathogen-associated molecular patterns (PAMPs). The ectodomain of a TLR directly senses a PAMP and the intracellular TIR domain dimerizes to initiate a signaling cascade. The TIR domains of TLR6 and TLR10, which belong to the TLR1 subfamily, have been structurally characterized in a dimer, whereas those of other subfamilies, including TLR15, have not been explored at the structural or molecular level. TLR15 is a TLR unique to birds and reptiles that responds to virulence-associated fungal and bacterial proteases. To reveal how the TLR15 TIR domain (TLR15TIR) triggers signaling, the crystal structure of TLR15TIR was determined in a dimeric form and a mutational study was performed. TLR15TIR forms a one-domain structure in which a five-stranded β-sheet is decorated by α-helices, as shown for TLR1 subfamily members. TLR15TIR exhibits substantial structural differences from other TLRs at the BB and DD loops and αC2 helix that are involved in dimerization. As a result, TLR15TIR is likely to form a dimeric structure that is unique in its intersubunit orientation and the contribution of each dimerizing region. Further comparative analysis of TIR structures and sequences provides insights into the recruitment of a signaling adaptor protein by TLR15TIR.